2004
DOI: 10.2337/diabetes.53.4.1082
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Impairs Skeletal Muscle Repair in Diabetic Rats

Abstract: Alongside increased proteolysis, the inability to repair damaged skeletal muscle is a characteristic feature of uncontrolled diabetes. This study evaluates the role of oxidative stress in muscle-specific gene regulatory regions and myosin chain synthesis in streptozotocin (STZ)-induced diabetic and ZDF rats. In the gastrocnemius muscle of diabetic rats, prooxidant compounds were seen to increase while antioxidant levels fell. Myogenic regulatory factors-Myo, myogenin, and Jun D-were also reduced, and muscle en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
107
0
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(130 citation statements)
references
References 50 publications
16
107
0
7
Order By: Relevance
“…Such an autoregulatory mechanism would help maintain increased levels of Foxa2 in STZ-treated WT mice and lower levels in Mstn Ϫ/Ϫ mice. In line with earlier findings (32,33,34), increased ROS was observed (and thus Anti-oxidant enzymes) in skeletal muscles of WT diabetic mice via TNF-␣, Nox1 (Fig. 1, A and B) and lipid peroxidation (data not shown).…”
Section: Discussionsupporting
confidence: 78%
“…Such an autoregulatory mechanism would help maintain increased levels of Foxa2 in STZ-treated WT mice and lower levels in Mstn Ϫ/Ϫ mice. In line with earlier findings (32,33,34), increased ROS was observed (and thus Anti-oxidant enzymes) in skeletal muscles of WT diabetic mice via TNF-␣, Nox1 (Fig. 1, A and B) and lipid peroxidation (data not shown).…”
Section: Discussionsupporting
confidence: 78%
“…Because of its accessibility, the gastrocnemius muscle has been previously studied to analyse the specific effects of DHEA on skeletal muscle (Hansen et al 1997;Aragno et al 2004;Campbell et al 2004). In the present study, a larger gastrocnemius size relative to total body mass was found in DHEA-treated rats compared with control ones.…”
Section: Discussionmentioning
confidence: 47%
“…Pacientes com diabetes apresentam estresse oxidativo sistêmico (Bonnard et al, 2008;Ramakrishna, Jailkhani, 2008) que envolve diferentes tecidos (Maritim et al, 2003;Matkovics et al, 1997), incluindo músculo esquelético (Aragno et al, 2004;Bravard et al, 2011;Gumieniczeket al, 2001;Matkovics et al, 1997). O estresse oxidativo nestas condições pode ser induzido pelas concentrações elevadas de glicose e AGL plasmáticos (Bloch-Damti, Bashan, 2005;Brownlee, 2001;Jellinger, 2007;Kraegen, Cooney, 2008) típicas da doença.…”
Section: Estresse Oxidativo No Diabetes: Um Componente Das Complicaçõunclassified
“…A capacidade de ligação ao sítio MEF-1 (do inglês muscle enhancer factor-1) do DNA (uma seqüência a qual se ligam MRFs e que é fundamental para a expressão de alguns genes específicos de músculo esquelético) é reduzida em ratos diabéticos e o estresse oxidativo é um dos mediadores deste efeito (Aragno et al,2004). Portanto, outros mecanismos, além da modulação da expressão dos MRFs, também comprometem a miogênese no diabetes.…”
unclassified